National Systems of Child Protection Understanding the International Variability and Context for Developing Policy and Practice - Merkel-Holguin, Lisa.; Fluke, John D.; Krugman, Richard D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume provides a wide spectrum description analysis of the contemporary and well established child protection systems in a range of countries, such as Australia, Canada, Netherlands and Spain. It presents a brief orientation about the public and private systems involved in protecting children in each country. Further the book identifies current key policy and implementation drivers that orient the systems of child protection, such as children's rights, family preservation, use of evidence and public health orientation. Finally it presents a critical analysis of the strengths and limitations of the systems, as well as, strategies for prospects for improving outcomes for children and their families. .
Chapter 1. Australia (Kim Oates) -- Chapter 2. Canada (Nico Trocmé, Antonio Esposito) -- Chapter 3. England (Nina Biehal, Helen Baldwin) -- Chapter 4. France (Flora Bolter) -- Chapter 5. Germany (Heinz Kindler, Eric Van Santen, Susanne Witte) -- Chapter 6. Ireland (Kenneth Burns) -- Chapter 7. Netherlands (Helen Bouma, Monica Lopez, Hans Grietens, Erik Knorth) -- Chapter 8. New Zealand (Paul Nixon, Michael Doolan) -- Chapter 9. Norway (Marit Skivness) -- Chapter 10. Spain (Monica Lopez, Jorge del Valle) -- Chapter 11. South Korea (Bong Joo Lee) -- Chapter 12. Switzerland (Andreas Jud, René Knüsel) -- Chapter 13. US (Richard Krugman, Laura Schwab-Reese, Karen Albright, Lisa Merkel-Holguin, John Fluke).
Keywords: Education; Children; Human rights; Quality of life; Family policy; Childhood Education; Human Rights; Quality of Life Research; Children, Youth and Family Policy